Summer temperature and emergency room visits due to urinary tract infection in South Korea: a national time-stratified case-crossover study - Jiwoo Park; Whanhee Lee; Dukhee Kang; Jieun Min; Hyemin Jang; Cinoo Kang; Dohoon Kwon; Youngrin Kwag; Eunhee Ha (BMC, 2024)
Abstract Background Although urinary tract infection (UTI) is a common and severe public health concern, and there are clear biological mechanisms between UTI and hot temperatures, few studies have addressed the association between hot temperatures and UTI. Methods We designed a time-stratified case-crossover study using a population-representative sample cohort based on the National Health Insurance System (NHIS) in South Korea. We obtained all NHIS-based hospital admissions through the emergency room (ER) due to UTI (using a primary diagnostic code) from 2006 to 2019. We assigned satellite-based reanalyzed daily summer (June to September) average temperatures as exposures, based on residential districts of beneficiaries (248 districts in South Korea). The conditional logistic regression was performed to evaluate the association between summer temperature and UTI outcome. Results A total of 4,436 ER visits due to UTI were observed during the summer between 2006 and 2019 among 1,131,714 NHIS beneficiaries. For 20% increase in summer temperatures (0-2 lag days), the odd ratio (OR) was 1.06 (95% CI: 1.02-1.10) in the total population, and the association was more prominent in the elderly (people aged 65 y or older; OR:1.11, 95% CI: 1.05-1.17), females (OR: 1.12, 95% CI: 1.05-1.19), and people with diabetes history (OR: 1.14, 95% CI: 1.07-1.23). The effect modification by household income was different in the total and elderly populations. Furthermore, the association between summer temperature and UTI increased during the study period in the total population. Conclusions Our results are consistent with the hypothesis that higher summer temperatures increase the risk of severe UTIs, and the risk might be different by sub-populations.